Topical Ascorbic Acid Ameliorates Oxidative Stress-Induced Corneal Endothelial Damage via Suppression of Apoptosis and Autophagic Flux Blockage - Yi-Jen Hsueh (Cells, 2020)
Compromised pumping function of the corneal endothelium, due to loss of endothelial cells, results in corneal edema and subsequent visual problems. Clinically and experimentally, oxidative stress may cause corneal endothelial decompensation after phacoemulsification. Additionally, in vitro and animal studies have demonstrated the protective effects of intraoperative infusion of ascorbic acid (AA). Here, we established a paraquat-induced cell damage model, in which paraquat induced reactive oxygen species (ROS) production and apoptosis in the B4G12 and ARPE-19 cell lines. We demonstrate that oxidative stress triggered autophagic flux blockage in corneal endothelial cells and that addition of AA ameliorated such oxidative damage. We also demonstrate the downregulation of Akt phosphorylation in response to oxidative stress. Pretreatment with ascorbic acid reduced the downregulation of Akt phosphorylation, while inhibition of the PI3K/Akt pathway attenuated the protective effects of AA. Further, we establish an in vivo rabbit model of corneal endothelial damage, in which an intracameral infusion of paraquat caused corneal opacity. Administration of AA via topical application increased its concentration in the corneal stroma and reduced oxidative stress in the corneal endothelium, thereby promoting corneal clarity. Our findings indicate a perioperative strategy of topical AA administration to prevent oxidative stress-induced damage, particularly for those with vulnerable corneal endothelia.